Aportaciones a la flora albarraciense. - Barrera Martínez, I. (Botanica Complutensis, 1996)
In this paper 45 taxa found in Sierra de Albarracín (Teruel, Spain) are commented, doc to its chorological iruportance or on account of recalling oíd references, olten forgolten. We remark Thalicthrum flavum subsp. costae, Vicia orobus, Laserpitiuni nestleri, Achillea pyrenaica, Eriophorum angustifoliun-z, etc.